Pre-lithiated titanium-based supercapacitor and preparation method thereof
By using prelithiated lithium titanate-based anode sheet and spherical porous carbon-based anode sheet in supercapacitors, combined with electric field prelithiation technology, the problems of cycle life and electrolyte usage of existing supercapacitors are solved, and the energy density and power density are improved.
Patent Information
- Application Number
- CN202411721426.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-14
AI Technical Summary
The existing supercapacitors have shortcomings in charge and discharge cycle life, and the electrolyte is used too much, resulting in high manufacturing costs and low energy density.
Prelithiated lithium titanate-based anode sheet and spherical porous carbon-based anode sheet are used to form a prelithiated lithium titanate-based anode sheet through the electric field prelithiation process, reducing the use of electrolyte, and improving energy density and cycling performance through the lithium ion transport mechanism.
The energy density and cycling performance of the supercapacitor are significantly improved, the electrolyte usage is reduced, and the manufacturing cost and power density are improved.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrochemical energy storage, and in particular relates to a pre-lithiation titanium-based supercapacitor and a preparation method thereof. Background Art
[0002] The continuous consumption of fossil fuels and the increasingly prominent environmental problems caused by it have sounded the alarm for global sustainable and healthy development. According to the "Carbon Emissions Report 2023" released by the International Energy Agency (IEA), global carbon dioxide emissions reached 37.4 billion tons in 2023, setting a record high. Human health and energy security are facing unprecedented challenges. It is urgent to develop low-carbon emission, clean and efficient new energy to meet the energy supply necessary for human production and life. In recent years, the installed capacity of clean energy such as wind power generation and solar power generation has increased day by day, and the battery-driven new energy electric vehicle industry has developed rapidly, and there is a huge demand for high-safety, high-energy density, high-power density, long-life, and low-cost electrochemical energy storage batteries.
[0003] Supercapacitors have the characteristics of high power density and long cycle life. They are widely used in electric vehicle starting power supply, new energy power generation frequency modulation, rail transit braking energy recovery system, wind power generation variable pitch, electronic instrumentation and other fields. Double-layer capacitors are a typical supercapacitor, which mainly uses the high specific surface area of porous carbon to physically adsorb charges for energy storage. Usually, the power density is ≥5kW / kg and the charge and discharge cycle life is 100,000 times, but its energy density is low (~5Wh / kg). The second is lithium-ion supercapacitors, which usually use porous carbon positive electrodes to adsorb electric cores and graphite negative electrodes to embed electric cores for energy storage. Its power density is ≥5kW / kg, the charge and discharge cycle life is 50,000 times, and the energy density is generally 15-20Wh / kg, but the energy density is still low. In addition, the lithium insertion capacity of the graphite negative electrode (~350mAh / g) is much higher than the anion adsorption capacity of the porous carbon positive electrode (~50mAh / g). If the capacity matching is to be achieved, it will bring great challenges to the electrode coating technology.
[0004] Compared with graphite negative electrode materials, lithium titanate (Li4Ti5O 12 , abbreviated as LTO) is a zero-strain negative electrode material. The material will not deform during the insertion and extraction of lithium ions, and has good cycle performance; its charge and discharge voltage is stable, and the lithium insertion / extraction potential is 1.55V vs.Li / Li +(Specific capacity ~ 165mAh / g), it is not easy to produce lithium dendrites, and has good safety performance; it has a high lithium ion diffusion coefficient, can be charged and discharged at a high rate, and has good power performance and low-temperature charge and discharge capabilities. By further coating the surface of the material with a carbon layer with good conductivity, the rate performance (large current charge and discharge capability, power density) can be further improved. Usually, people combine the lithium titanate negative electrode with the activated carbon positive core. When charging, the lithium ions in the electrolyte of the formed lithium titanate supercapacitor are electrochemically embedded into the lithium titanate negative electrode, and the anions are physically adsorbed to the activated carbon positive electrode. When discharging, the negative electrode releases lithium ions back into the electrolyte, and the positive electrode releases anions back into the electrolyte. Studies have found that this type of supercapacitor is based on the consumption of electrolyte, and the charge and discharge cycle life is relatively low. In order to ensure the cycle life, the amount of electrolyte injected is often >3g / Ah, resulting in high manufacturing costs. At the same time, the weight of the device increases, thereby reducing the energy density. Summary of the invention
[0005] In order to solve the above problems, the present invention provides a pre-lithiation titanium-based supercapacitor and a preparation method thereof.
[0006] To achieve the above purpose, the present invention adopts the following technical solution:
[0007] A pre-lithiated titanium-based supercapacitor comprises a negative electrode, a positive electrode, a diaphragm, an electrolyte and a shell. The negative electrode is a pre-lithiated lithium titanate-based negative electrode, the pre-embedded lithium amount of the electrode is 150-165 mAh / g, the ratio of the total capacity of the negative electrode to the total capacity of the positive electrode is 1.9-3.5, and the electrolyte injection amount is 1.5-2.5 g / Ah.
[0008] The pre-lithiated lithium titanate-based negative electrode sheet is prepared by coating a negative electrode slurry containing a lithium titanate / carbon composite material on a current collector, and then embedding lithium ions into the negative electrode sheet through an electric field with a lithium auxiliary electrode to form a pre-lithiated lithium titanate-based negative electrode sheet.
[0009] The pre-lithiated lithium titanate-based negative electrode sheet is prepared by mixing the lithium titanate / carbon composite material with a conductive agent and a binder, adding a solvent to prepare a negative electrode slurry, and then coating the mixture on a current collector to obtain a non-pre-lithiated lithium titanate-based negative electrode sheet;
[0010] The non-pre-lithiated lithium titanate-based negative electrode sheet and the lithium auxiliary electrode are separated by a diaphragm and placed in an electrolyte. The non-pre-lithiated lithium titanate-based negative electrode sheet and the lithium auxiliary electrode are then connected to a charge and discharge instrument respectively. Under the action of the electric field, lithium ions are embedded in the non-pre-lithiated lithium titanate-based negative electrode sheet to form a pre-lithiated lithium titanate-based negative electrode sheet.
[0011] The negative electrode slurry is mixed with a negative electrode active material, a conductive agent and a binder in a weight ratio of 90-95:1.5-5:1.5-5;
[0012] The electric field pre-lithiation process is as follows: a non-pre-lithiated lithium titanate-based negative electrode sheet is separated from a lithium auxiliary electrode by a diaphragm, placed in an electrolyte, and then the non-pre-lithiated lithium titanate-based negative electrode sheet and the lithium auxiliary electrode are respectively connected to a charge and discharge instrument, and discharged at a rate of 0.2C to embed lithium ions into the non-pre-lithiated lithium titanate-based negative electrode sheet to form a pre-lithiated lithium titanate-based negative electrode sheet.
[0013] The diaphragm material is one of polypropylene, polyethylene and cellulose.
[0014] The positive electrode sheet is prepared by mixing spherical porous carbon as a positive electrode active material with a conductive agent and a binder, adding a solvent to prepare a positive electrode slurry, and then coating the spherical porous carbon-based positive electrode sheet on a current collector; wherein the weight ratio of the positive electrode active material, the conductive agent, and the binder is 85-95:2.5-7.5:2.5-7.5.
[0015] The binders in the negative electrode slurry and the positive electrode slurry may be the same or different and may be one or more of polyvinylidene fluoride, polytetrafluoroethylene, styrene-butadiene latex, and sodium carboxymethyl cellulose;
[0016] The conductive agents in the negative electrode slurry and the positive electrode slurry may be the same or different and may be one or more of conductive carbon black, conductive graphite, graphene, carbon nanotubes, and graphitized carbon fibers.
[0017] A method for preparing a pre-lithiated titanium-based supercapacitor comprises alternately stacking the positive and negative electrode sheets, providing a diaphragm between two adjacent sheets, assembling a winding core, and placing the positive electrode sheets on both sides of the winding core; then vacuum drying the assembled winding core and placing it in a shell, injecting an electrolyte into the shell, and sealing the shell.
[0018] The pre-lithiated lithium titanate-based negative electrode sheet is prepared by coating a negative electrode slurry containing a lithium titanate / carbon composite material on a current collector, drying, rolling, cutting, and vacuum baking, and then inserting lithium ions into the negative electrode sheet through an electric field with a lithium auxiliary electrode to form a pre-lithiated lithium titanate-based negative electrode sheet;
[0019] The positive electrode sheet is prepared by mixing spherical porous carbon as a positive electrode active material with a conductive agent and a binder, adding a solvent to prepare a positive electrode slurry, and then coating it on a current collector, drying, rolling, cutting, and vacuum baking to obtain a spherical porous carbon-based positive electrode sheet.
[0020] The advantages and positive effects of the present invention are:
[0021] The present invention uses lithium titanate Li4Ti5O 12 The negative electrode is pre-lithium-embedded to generate Li7Ti5O 12 , forming a pre-lithiated lithium titanate-based negative electrode, which stabilizes its potential at 1.55V vs.Li / Li +, and then combined with a spherical porous carbon-based positive core to form a new type of pre-lithiated titanium-based supercapacitor. During discharge, lithium ions are deintercalated from the pre-lithiated lithium titanate-based negative electrode, and under the action of the electric field, they migrate to the spherical porous carbon-based positive electrode and are physically adsorbed on the surface of the spherical porous carbon-based positive electrode. During charging, lithium ions are desorbed from the positive electrode surface and return to the negative electrode. The pre-lithiated titanium-based supercapacitor of the present invention is based on a lithium ion transport mechanism and does not consume the injected electrolyte, thereby reducing the amount of electrolyte used. The energy density and cycle performance of the supercapacitor are significantly improved. In addition, the positive electrode uses spherical porous carbon with a reasonable specific surface area to ensure that lithium ions are adsorbed to the positive electrode surface from different directions, thereby improving the rate performance and power density. DETAILED DESCRIPTION
[0022] The specific implementation modes of the present invention are further described below in conjunction with examples. It should be noted that the specific implementation modes described here are only for illustrating and explaining the present invention, and are not limited to the present invention.
[0023] Example 1
[0024] (1) Preparation of pre-lithiated lithium titanate-based negative electrode sheets: The negative electrode active material lithium titanate / carbon composite material (commercially available) is mixed with conductive carbon black and binder polyvinylidene fluoride in a weight ratio of 92:3:5, and the solvent N-methyl-2-pyrrolidone is added to prepare a negative electrode slurry, which is then coated on an aluminum foil current collector. After drying, rolling, and cutting, the size of the sheet is 19.7 cm × 14.7 cm, and vacuum baking is performed to prepare a non-pre-lithiated lithium titanate-based negative electrode sheet.
[0025] The non-pre-lithiated lithium titanate-based negative electrode sheet was separated from the lithium auxiliary electrode by a diaphragm and placed in an electrolyte of 1.2 mol / L lithium hexafluorophosphate / propylene carbonate-dimethyl carbonate, ethyl methyl carbonate, vinylene carbonate, methylene disulfonate, and p-toluenesulfonyl isocyanate (solvent weight ratio of 20:40:40:1:0.75:0.25). The non-pre-lithiated lithium titanate-based negative electrode sheet and the lithium auxiliary electrode were then connected to a charge and discharge instrument and discharged at a rate of 0.2C to embed lithium ions into the non-pre-lithiated lithium titanate-based negative electrode sheet to form a pre-lithiated lithium titanate-based negative electrode sheet with a pre-embedded lithium amount of 160 mAh / g.
[0026] (2) Preparation of spherical porous carbon-based positive electrode sheet: The positive electrode active material asphalt-based spherical porous carbon is mixed with conductive carbon black and a binder (a mixture of styrene-butadiene latex and sodium carboxymethyl cellulose in a weight ratio of 3.5:1.5) in a weight ratio of 90:5:5, and the mixture is mixed with deionized water as a solvent to form a positive electrode slurry, which is then coated on an aluminum foil current collector, dried, rolled, and cut into pieces with a size of 20.1 cm × 15.1 cm, and vacuum-baked to form a spherical porous carbon-based positive electrode sheet. At this time, the ratio of the total capacity of the negative electrode sheet to the total capacity of the positive electrode sheet is 2.5.
[0027] (3) Assembly: A cellulose separator is selected as the separator, and the sheets are stacked in the order of spherical porous carbon-based positive electrode sheet / / separator / / pre-lithiated lithium titanate-based negative electrode sheet / / separator / / spherical porous carbon-based positive electrode sheet / / separator / / pre-lithiated lithium titanate-based negative electrode sheet / / separator / / spherical porous carbon-based positive electrode sheet... to form a roll core, and the outermost two sides of the roll core always remain spherical porous carbon-based positive electrode sheets.
[0028] (4) Liquid injection and sealing: After vacuum drying, the core is placed in a shell, and an electrolyte of 1.2 mol / L lithium hexafluorophosphate / propylene carbonate-dimethyl carbonate, ethyl methyl carbonate, vinylene carbonate, methylene disulfonate, and p-toluenesulfonyl isocyanate (solvent weight ratio 20:40:40:1:0.75:0.25) is injected into the shell. The electrolyte injection amount is 2 g / Ah, and the shell is sealed to obtain a pre-lithiated titanium-based supercapacitor.
[0029] (5) Test results: It has been determined that the discharge capacity of the titanium-based supercapacitor at a 1C rate current is 10.8Ah, the mass energy density is 56.5Wh / kg, the power density at a 10C rate current is 8.6kW / kg, the 10C discharge capacity / 1C discharge capacity is 98.2%, and the capacity retention rate after 50,000 charge and discharge cycles at 10C is 87.8%.
[0030] Example 2
[0031] The amount of pre-embedded lithium in Example 1 was changed to 150 mAh / g, and the rest remained unchanged.
[0032] Test results: It was determined that the discharge capacity of the titanium-based supercapacitor at 1C rate current is 10.7Ah, the mass energy density is 56.3Wh / kg, the power density at 10C rate current is 8.4kW / kg, the 10C discharge capacity / 1C discharge capacity is 97.8%, and the capacity retention rate after 50,000 charge and discharge cycles at 10C is 87.3%
[0033] Example 3
[0034] The amount of pre-embedded lithium in Example 1 was changed to 165 mAh / g, and the rest remained unchanged.
[0035] Test results: It has been determined that the discharge capacity of the titanium-based supercapacitor at a 1C rate current is 10.8Ah, the mass energy density is 56.3Wh / kg, the power density at a 10C rate current is 8.4kW / kg, the 10C discharge capacity / 1C discharge capacity is 97.9%, and the capacity retention rate after 50,000 charge and discharge cycles at 10C is 87.9%.
[0036] Example 4
[0037] The ratio of the total capacity of the negative electrode sheet to the total capacity of the positive electrode sheet in Example 1 is changed to 2, and the rest remains unchanged.
[0038] Test results: It has been determined that the discharge capacity of the titanium-based supercapacitor at a 1C rate current is 10.6Ah, the mass energy density is 60.3Wh / kg, the power density at a 10C rate current is 8.5kW / kg, the 10C discharge capacity / 1C discharge capacity is 97.8%, and the capacity retention rate after 50,000 charges and discharges at 10C is 85.6%.
[0039] Example 5
[0040] The ratio of the total capacity of the negative electrode sheet to the total capacity of the positive electrode sheet in Example 1 was changed to 3.2, and the rest remained unchanged. Test results: It was determined that the discharge capacity of the titanium-based supercapacitor at a 1C rate current was 10.6Ah, the mass energy density was 51.6Wh / kg, the power density at a 10C rate current was 8.2kW / kg, the 10C discharge capacity / 1C discharge capacity was 97.1%, and the capacity retention rate after 50,000 10C charge and discharge cycles was 88.1%.
[0041] Example 6
[0042] The electrolyte injection amount in Example 1 was changed to 1.5 g / Ah, and the rest remained unchanged.
[0043] Test results: It has been determined that the discharge capacity of the titanium-based supercapacitor at a 1C rate current is 10.8Ah, the mass energy density is 62.5Wh / kg, the power density at a 10C rate current is 8.6kW / kg, the 10C discharge capacity / 1C discharge capacity is 98.2%, and the capacity retention rate after 50,000 charge and discharge cycles at 10C is 82.5%.
[0044] Example 7
[0045] The electrolyte injection amount in Example 1 was changed to 2.5 g / Ah, and the rest remained unchanged.
[0046] Test results: It has been determined that the discharge capacity of the titanium-based supercapacitor at a 1C rate current is 10.9Ah, the mass energy density is 52.7Wh / kg, the power density at a 10C rate current is 8.7kW / kg, the 10C discharge capacity / 1C discharge capacity is 98.6%, and the capacity retention rate after 50,000 charges and discharges at 10C is 89.9%.
[0047] Comparative Example 1
[0048] The amount of pre-embedded lithium in Example 1 was changed to 140 mAh / g, and the rest remained unchanged.
[0049] Test results: It has been determined that the discharge capacity of the titanium-based supercapacitor at a 1C rate current is 9.5Ah, the mass energy density is 48.1Wh / kg, the power density at a 10C rate current is 7.6kW / kg, the 10C discharge capacity / 1C discharge capacity is 96.3%, and the capacity retention rate after 50,000 charge and discharge cycles at 10C is 76.4%.
[0050] Comparative Example 2
[0051] The ratio of the total capacity of the negative electrode sheet to the total capacity of the positive electrode sheet in Example 1 was changed to 1.5, and the rest remained unchanged.
[0052] Test results: It has been determined that the discharge capacity of the titanium-based supercapacitor at a 1C rate current is 10.3Ah, the mass energy density is 54.2Wh / kg, the power density at a 10C rate current is 7.5kW / kg, the 10C discharge capacity / 1C discharge capacity is 96.2%, and the capacity retention rate after 50,000 charges and discharges at 10C is 73.1%.
[0053] Comparative Example 3
[0054] The ratio of the total capacity of the negative electrode sheet to the total capacity of the positive electrode sheet in Example 1 is changed to 4, and the rest remains unchanged.
[0055] Test results: It has been determined that the discharge capacity of the titanium-based supercapacitor at a 1C rate current is 10.8Ah, the mass energy density is 46.3Wh / kg, the power density at a 10C rate current is 7.3kW / kg, the 10C discharge capacity / 1C discharge capacity is 95.1%, and the capacity retention rate after 50,000 charge and discharge cycles at 10C is 88.3%.
[0056] Comparative Example 4
[0057] The electrolyte injection amount in step (4) of Example 1 was changed to 1 g / Ah, and the rest remained unchanged.
[0058] Test results: It has been determined that the discharge capacity of the titanium-based supercapacitor at a 1C rate current is 10.3Ah, the mass energy density is 59.5Wh / kg, the power density at a 10C rate current is 8.7kW / kg, the 10C discharge capacity / 1C discharge capacity is 98.3%, and the capacity retention rate after 50,000 charge and discharge cycles at 10C is 67.5%.
[0059] Comparative Example 5
[0060] The electrolyte injection amount in step (4) of Example 1 was changed to 3 g / Ah, and the rest remained unchanged.
[0061] Test results: It has been determined that the discharge capacity of the titanium-based supercapacitor at a 1C rate current is 10.8Ah, the mass energy density is 53.6Wh / kg, the power density at a 10C rate current is 8.7kW / kg, the 10C discharge capacity / 1C discharge capacity is 98.5%, and the capacity retention rate after 50,000 charges and discharges at 10C is 88.9%.
[0062] Comparative Example 6
[0063] The asphalt-based spherical porous carbon in Example 1 was changed to irregular porous carbon, and the rest remained unchanged.
[0064] Test results: It has been determined that the discharge capacity of the titanium-based supercapacitor at a 1C rate current is 10.8Ah, the mass energy density is 56.5Wh / kg, the power density at a 10C rate current is 6.7kW / kg, the 10C discharge capacity / 1C discharge capacity is 95.3%, and the capacity retention rate after 50,000 charge and discharge cycles at 10C is 83.1%.
[0065] Comparative Example 7
[0066] Preparation of lithium-ion supercapacitors
[0067] (1) Preparation of positive electrode for lithium-ion supercapacitor: a porous carbon material with high specific surface area (commercially available, with a specific surface area of 1560 m 2 / g, with a specific capacity of 50 mAh / g) was mixed with conductive carbon black and binder polyvinylidene fluoride in a weight ratio of 92:3:5, and the solvent N-methyl-2-pyrrolidone was added to prepare the negative electrode slurry, which was then coated on an aluminum foil current collector, dried, rolled, and cut into pieces with a size of 19.7 cm × 14.7 cm, and vacuum baked to make the positive electrode sheet.
[0068] (2) Preparation of negative electrode sheets for lithium-ion supercapacitors: The negative electrode active material graphite material (commercially available, with a specific capacity of 350 mAh / g) is mixed with conductive carbon black and a binder (a mixture of styrene-butadiene latex and sodium carboxymethyl cellulose in a weight ratio of 3.5:1.5) in a weight ratio of 90:5:5, and then added with deionized water as a solvent to prepare a negative electrode slurry. The slurry is then coated on a copper foil current collector, dried, rolled, and cut into pieces with a size of 20.1 cm × 15.1 cm. The negative electrode sheet is made by vacuum baking. The weight of the slurry coated per unit area of the negative electrode sheet is 1 / 7 of that of the positive electrode.
[0069] (3) Assembly: A cellulose separator is used as the separator, and the sheets are stacked in the order of positive electrode sheet / / separator / / negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet / / separator / / positive electrode sheet... to form a winding core, and the outermost two sides of the winding core are always kept as positive electrode sheets.
[0070] (4) Liquid injection and sealing: After vacuum drying the core, place it in a shell and inject an electrolyte of 1.2 mol / L lithium hexafluorophosphate / propylene carbonate-dimethyl carbonate, ethyl methyl carbonate, vinylene carbonate, methane disulfonic acid methylene ester, p-toluenesulfonyl isocyanate (solvent weight ratio 20:40:40:1:0.75:0.25) into the shell. The electrolyte injection amount is 2g / Ah and sealed, i.e., a lithium-ion supercapacitor. (5) Test results: After measurement, the discharge capacity of the lithium-ion supercapacitor at a 1C rate current is 8.6Ah, the mass energy density is 16.8Wh / kg, the power density at a 10C rate current is 5.8kW / kg, the 10C discharge capacity / 1C discharge capacity is 78.6%, and the capacity retention rate after 50,000 10C charge and discharge cycles is 72.1%.
[0071] As described in Comparative Example 7, the lithium-ion supercapacitor constructed by using the existing technology, that is, the positive electrode adopts a high specific surface area porous carbon active material and the negative electrode adopts a graphite active material, has an energy density, power density, 10C discharge capacity / 1C discharge capacity and 10C charge and discharge 50,000 times capacity retention rate that are lower than the pre-lithiation titanium-based supercapacitor described in Example 1.
[0072] In summary, the present invention combines a pre-lithiated lithium titanate-based negative electrode sheet and a spherical porous carbon-based positive electrode sheet to form a novel pre-lithiated titanium-based supercapacitor, which is based on a lithium ion transport mechanism and does not consume the injected electrolyte, thereby reducing the amount of electrolyte used. The energy density and cycle performance of the supercapacitor are significantly improved. In addition, the positive electrode uses spherical porous carbon with a reasonable specific surface area to ensure that lithium ions are adsorbed to the positive electrode surface from different directions, thereby improving the rate performance and power density.
[0073] The above-mentioned embodiments only represent several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the present invention patent shall be subject to the attached claims.
Claims
1. A pre-lithiation titanium-based supercapacitor, comprising a negative electrode sheet, a positive electrode sheet, a diaphragm, an electrolyte and a shell, characterized in that: The negative electrode sheet is a pre-lithiated lithium titanate-based negative electrode sheet, the pre-embedded lithium content of the electrode sheet is 150-165 mAh / g, the ratio of the total capacity of the negative electrode sheet to the total capacity of the positive electrode sheet is 1.9-3.5, and the electrolyte injection amount is 1.5-2.5 g / Ah.
2. The pre-lithiation titanium-based supercapacitor according to claim 1, characterized in that: The pre-lithiated lithium titanate-based negative electrode sheet is prepared by coating a negative electrode slurry containing a lithium titanate / carbon composite material on a current collector, and then embedding lithium ions into the negative electrode sheet through an electric field with a lithium auxiliary electrode to form a pre-lithiated lithium titanate-based negative electrode sheet.
3. The pre-lithiation titanium-based supercapacitor according to claim 2, characterized in that: The pre-lithiated lithium titanate-based negative electrode sheet is prepared by mixing the lithium titanate / carbon composite material with a conductive agent and a binder, adding a solvent to prepare a negative electrode slurry, and then coating the mixture on a current collector to obtain a non-pre-lithiated lithium titanate-based negative electrode sheet; The non-pre-lithiated lithium titanate-based negative electrode sheet and the lithium auxiliary electrode are separated by a diaphragm and placed in an electrolyte. The non-pre-lithiated lithium titanate-based negative electrode sheet and the lithium auxiliary electrode are then connected to a charge and discharge instrument respectively. Under the action of the electric field, lithium ions are embedded in the non-pre-lithiated lithium titanate-based negative electrode sheet to form a pre-lithiated lithium titanate-based negative electrode sheet.
4. The pre-lithiation titanium-based supercapacitor according to claim 3, characterized in that: The negative electrode slurry is a mixture of a negative electrode active material, a conductive agent and a binder in a weight ratio of 90-95:1.5-5:1.5-5.
5. The pre-lithiation titanium-based supercapacitor according to claim 1 or 3, characterized in that: The diaphragm material is one of polypropylene, polyethylene and cellulose.
6. The pre-lithiation titanium-based supercapacitor according to claim 1, characterized in that: The positive electrode sheet is prepared by mixing spherical porous carbon as a positive electrode active material with a conductive agent and a binder, adding a solvent to prepare a positive electrode slurry, and then coating the spherical porous carbon-based positive electrode sheet on a current collector; wherein the weight ratio of the positive electrode active material, the conductive agent, and the binder is 85-95:2.5-7.5:2.5-7.
5.
7. The pre-lithiation titanium-based supercapacitor according to claim 3 or 6, characterized in that: The binders in the negative electrode slurry and the positive electrode slurry may be the same or different and may be one or more of polyvinylidene fluoride, polytetrafluoroethylene, styrene-butadiene latex, and sodium carboxymethyl cellulose; The conductive agents in the negative electrode slurry and the positive electrode slurry may be the same or different and may be one or more of conductive carbon black, conductive graphite, graphene, carbon nanotubes, and graphitized carbon fibers.
8. A method for preparing a pre-lithiated titanium-based supercapacitor according to claim 1, characterized in that: The positive and negative electrode sheets as described in claim 1 are alternately stacked, a separator is provided between two adjacent sheets, and a winding core is assembled, with the positive electrode sheets being provided on both sides of the winding core; the assembled winding core is then vacuum dried and placed in a shell, and an electrolyte is injected into the shell, and the shell is sealed.
9. The method for preparing a pre-lithiated titanium-based supercapacitor according to claim 8, characterized in that: The pre-lithiated lithium titanate-based negative electrode sheet is prepared by coating a negative electrode slurry containing a lithium titanate / carbon composite material on a current collector, drying, rolling, cutting, and vacuum baking, and then inserting lithium ions into the negative electrode sheet through an electric field with a lithium auxiliary electrode to form a pre-lithiated lithium titanate-based negative electrode sheet; The positive electrode sheet is prepared by mixing spherical porous carbon as a positive electrode active material with a conductive agent and a binder, adding a solvent to prepare a positive electrode slurry, and then coating it on a current collector, drying, rolling, cutting, and vacuum baking to obtain a spherical porous carbon-based positive electrode sheet.